Development of Student Work Sheet (LKPD) Based on Indonesian Realistic Mathematics Education (PMRI) On the Subject Subject Area of Surface Building Side Rooms for Students of SMP Amayatul Huda T.P 2021/2022 - Ananda, Febri; Elfrianto, Elfrianto (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2023)
This research is a research on the development of Student Worksheets (LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on the subject of curved side shapes. This study aims to 1) describe the product quality of Student Worksheets (LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on the subject of curved side shapes. 2) describe the results of the development of Student Worksheets (LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on the subject of curved side spaces. In this study, researchers used research and development procedures according to Sugiyono which have been modified. The subjects of this study were students of class IX at SMP Amayatul Huda, Kec. Medan, Deli Kel. Labuhan Deli. The object in this research is the Student Worksheet (LKPD) which was developed by the researcher. The data collection technique used is the results of validation and interview results related to student responses regarding the use of Student Worksheets (LKPD) products. The development procedures in this study include: (1) potentials and problems; (2) Data collection; (3) Product design; (4) Design validation; (5) Design revision; (6) Product trials. The product validation results for Student Worksheets (LKPD) developed by researchers were 3.9 and 4.2 and were included in the good category. The Student Worksheet (LKPD) which was developed by the researcher received a positive response from class IX students at SMP Amayatul Huda.